PENGEMBANGAN MEDIA INTERAKTIF BERBASIS CANVA PADA PEMBELAJARAN MUFRODAT KELAS IV MIN 2 KABUPATEN GORONTALO - Manangin, Nelpia; Bahri, Ratni Bt. H.; Iman, Muhammad Nur (Yayasan Daarul Qimmah Gorontalo, 2024)
This research aims to develop and produce interactive educational media using Canva for Arabic vocabulary (mufrodat) learning for fourth-grade students at MIN 2 in Gorontalo Regency. The impetus for this research originates from noticing that technology is not widely integrated into the Arabic learning process, leading to less effective language acquisition and difficulties for students in understanding vocabulary. The research employs a Research and Development (R&D) approach, specifically following the ADDIE model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. The methods for data collection included observation, interviews, and documentation, and the data were confirmed by specialists in media, content, and language. Trials were conducted with both small and large groups to evaluate the efficacy of the educational tools. The results indicate that the interactive educational media utilizing Canva is highly feasible, with validation scores of 96%, 92%, and 95% from media, content, and language experts, respectively. Trials with small and large groups yielded positive responses with average percentages of 81% and 84%. Analysis of pre-test and post-test data employing the Wilcoxon Signed-Rank Test indicated a notable enhancement in students' vocabulary comprehension after using the Canva-based learning media, with a Z value of -4.024 and a two-tailed asymptotic significance of 0.000. In conclusion, the Canva-based interactive learning media is effective in enhancing students' abilities in learning Arabic vocabulary.